Drug Sales Application Program at Y Farma in Kuningan - Rafi Farizki (Journal of Business, Social and Technology, 2020)
In order to improve customer service and satisfaction. As well as to follow the competition of the present, then in the process of data processing must be fast and accurate. Therefore, informatics technology in the form of computers is very important in the midst of the company's activities in an effort to improve the company's performance in achieving progress. For data collection by this method, the author may gather information relevant to topics and problems that will or is being researched, by studying scientific books, the internet, scientific papers, theses and dissertations, yearbooks, rules, encyclopedias and written and electronic sources.